Preliminary Phytochemical Screening and Evaluation of in vitro Anthelmintic Activity of Blepharis maderaspatensis Leaf - Aiswarya, V.; Nithya, Sermuga Pandian; Priyan, E.D Giridar; V, Manikandan (Journal of Pharmacy Practice and Community Medicine, 2026)
Background: Helminth infections continue to be a major public health and the veterinary problem, especially in the tropical and subtropical regions. In recent years, the resistance is commonly used anthelmintic drugs has increased which has reduced their therapeutic effectiveness. Because there is a need to explore alternative sources of antiparasitic agents. Medicinal plants that contain a wide range of secondary metabolites and considered a promising source for the development of new anthelmintic compounds. Blepharis maderaspatensis is a medical plant traditionally used in indigenous medicine for treating inflammatory conditions and wound healing, but its anthelmintic activity has not been studied extensively. Purpose: The aim of this study was to perform a preliminary phytochemical analysis of Blepharis maderaspatensis leaf extracts prepared by using solvents with different polarities and to evaluate the in vitro anthelmintic activity using Phereetima posthuma as the experimental model. Materials and Methods: The shade dried leaf powder was extracted sequentially using petroleum ether, chloroform, ethyl acetate, ethanol and distilled water. Qualitative phytochemical screening was carried out using standard chemical tests to identify the major secondary metabolites present in the extracts. The in vitro anthelmintic activity was evaluated by recording the time taken for paralysis and death of the adult earthworms. The three worms were used in each treatment group and all experiments were performed in triplicate. Piperazine citrate was used as the standard reference drug. Results: The phytochemical analysis showed the presence of flavonoids, alkaloids, tannins, phenolic compounds, glycosides, steroids, terpenoids and anthraquinones in different extracts. Among all, the ethanolic extract showed the highest anthelmintic activity, cause the paralysis at 12.08 sec and death at 20.50 sec. The chloroform extract showed moderate activity, while the ethyl acetate extract had the least effect. Interestingly, ethanolic extract produced faster paralysis compared to piperazine citrate, suggesting strong neuromuscular interface. Conclusion: The results of this study show the Belpharis maderaspatensis has significant in vitro anthelmintic activity, with the ethanolic extract showing better effectiveness than the other extracts. This activity may be due to the combined action of different phytoconstituents present in the plant. Further studies, including isolation of active compounds, dose response evaluation and in vivo studies are needed to confirm its therapeutic potential.
Keywords: Anthelmintic Activity; Anthelmintic Resistance; Blepharis maderaspatensis; Medicinal; Plants; Pheretima Posthuma; Phytochemical Screening